ANTHROPOMETRY AND ACOUSTIC REVIEWAT AUDITORIUMSEAT OF GIRI NATA MANDALA CULTURE CENTER - Ida Ayu Anindya Chintya Aridewi; Ida Ayu Dyah Maharani; I Gede Mugi Raharja (Ide dan Dialog Desain Indonesia (Idealog), 2023)
Chairs in the auditorium room are important furniture that is used for a long time by the audience. So it is important to know the anthropometric size of the auditorium seats to determine user comfort. inaddition to anthropometry, auditorium chairs are used to support sound comfort. This study focuses ontheanthropometry of the auditorium seats Giri Nata Mandala Puspem Badung Cultural Center and chairs assupporting the acoustic quality of the auditorium. The purpose of this study was to examine the designof auditorium seats in terms of anthropometry as well as the identification and measurement of seats in terms of interior that af ect acoustics. The method used is quantitative descriptive method. Data obtained basedonobservation, direct measurement and dissemination of questionnaires to users. The Data were analyzed usinganthropometric theory as well as theories related to interior acoustics. The results obtained are theauditorium seats have been designed in accordance with the standards of the auditoriumseats withanthropometry following the standards of Indonesia. So that the chair is comfortable to use for a longtime. In terms of interior acoustics, the auditorium seats have met the standards. However, there are someinconveniences when the auditorium is used for events. Audience in the front row to the middle of thecorridor on the left and right complained that the sound was too loud to make the seats shaking. In addition, vibrations in the seats are felt when other spectators pass by in the corridor. For further improvements, it would be better to pay attention to the sound volume and material of the chair or floor to reduce vibrationonthe chair. Keywords: Anthropometry, Acoustics, Auditorium Chair